2000
DOI: 10.1007/s005310050324
|View full text |Cite
|
Sign up to set email alerts
|

Physical weathering of marbles caused by anisotropic thermal expansion

Abstract: Marbles as building stones as well as in their natural environments show complex weathering phenomena. The most important damage scenario is based on the highly anisotropic thermal expansion coefficient a of calcite, i.e. extreme expansion parallel and contraction normal to the crystallographic c-axis. Therefore, the rock fabric and especially the latticepreferred orientation (texture) of calcite and/or dolomite as the predominant mineral phases in marbles have a significant influence on the mechanical weather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
142
0
14

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 241 publications
(161 citation statements)
references
References 22 publications
(19 reference statements)
5
142
0
14
Order By: Relevance
“…Therefore, the grain size cannot be the most important factor for marble degradation (see discussion in Zeisig et al 2002) as was suggested by Tschegg et al (1999). The grain shape anisotropy significantly triggers the thermal degradation, as shown for several samples by Siegesmund et al (2000) or Ruedrich et al (2001). Thus, grain boundary cracking is the most prominent factor for marble degradation; a substantial part of the observed directional dependence of residual strain must be attributed to shape fabrics.…”
Section: Thermal Expansion and Modal Compositionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, the grain size cannot be the most important factor for marble degradation (see discussion in Zeisig et al 2002) as was suggested by Tschegg et al (1999). The grain shape anisotropy significantly triggers the thermal degradation, as shown for several samples by Siegesmund et al (2000) or Ruedrich et al (2001). Thus, grain boundary cracking is the most prominent factor for marble degradation; a substantial part of the observed directional dependence of residual strain must be attributed to shape fabrics.…”
Section: Thermal Expansion and Modal Compositionmentioning
confidence: 99%
“…Thermally treated marbles which do not return to initial length changes after heating or cooling can show an inelastic residual strain even as a result of very small temperature changes (Battaglia et al 1993). In a more systematic study, Siegesmund et al (1999Siegesmund et al ( , 2000, Zeisig et al (2002) or Ruedrich (2003) showed, that, depending on the length change behaviour under thermal treatment four distinct groups of marbles can be distinguished. Bortz et al (1988) and Thomasen and Ewart (1984) concluded that a variation in moisture contents may be responsible for the deformation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Carrara marble was selected for the tests, because this lithotype was widely used in historic architecture and sculpture all over Europe, so that it is often adopted in research studies on marble deterioration and conservation [1,[24][25][26][27]. A slab with 50×50×1 cm 3 size was purchased from BasketweaveMosaics.com (USA) and sawn into cubic and prismatic specimens.…”
Section: Marblementioning
confidence: 99%